Investigation of bandgap energies of a single phase Zn(₁₋ₓ)CuₓO nanoparticles / Suraya Ahmad Kamil … [et al.] - Ahmad Kamil, Suraya; Kamarulzaman, Che Norlida; Mahat, Annie Maria; Mustaffa, Nur Amalina (Research Management Institute (RMI), 2012)
ZnO nanostructures are extensively studied due to their attractive characteristics and behaviour with wide band gap (3.4 eV) and large exciton binding energy (60 meV) Recently, there have been a lot of interests in studying modified ZnO nanostructures. The prospect of magnetically controlled operation of semiconductor devices has provoked intensive research to develop transition metal doped wide-band-gap semiconductors,i.e. diluted magnetic semiconductors (DMS) with room temperature ferromagnetism. Among transition metals, Cu is an especially interesting dopant because that Cu-related compounds are not strongly ferromagnetic. Transition metal-doped ZnO offers the potential for realizing room temperature operation of active spintronic devices as well as rich and fascinating fundamental physics…